Characteristics of biofilm formation from mixed microflora at mesophilic and thermophilic fermentative hydrogen production / Lam Wai Fung - Fung, Lam Wai; Lutpi, Nabilah Aminah; Shian, Wong Yee; Tengku Izhar, Tengku Nuraiti (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Biofilm-based systems have been extensively used as immobilized cell systems as they enhance the reaction rates and population dynamics. Therefore, this study was done to characterize the biofilm formation from anaerobic sludge for fermentative hydrogen (H2) production at mesophilic and thermophilic conditions. This study has been focusing on the development of mixed microflora biofilms whereby the physical and chemical characteristics of the biofilm will be studied. Several tests were done to characterize the biofilm formation, which included the Fourier transform infrared spectroscopy (FTIR) to test the functional group present in the immobilized cell, analysis on the gas produced by the immobilised cells using a gas analyser, and lastly analysis on the chemical compositions presence in the extracellular polymeric substances (EPS) of biofilm. This study had identified that the highest amount of gas collected which representing hydrogen is 470 ppm with the condition of 60 °C with GAC. From the FTIR analysis, the functional group exist in two peak 3308.3cm-1 and 1637.12cm-1 are the hydroxyl (O-H) group and the combination of C–N + N–H groups in proteins respectively. The transmission of each peak from the FTIR result, and the concentration of the carbohydrate and protein in the extracted EPS had increased with the increasing of the fermentation day, indicates that the physical and chemical properties of the EPS may change more than expected during biofilm growth and alteration.